LED chip-on-board package with high colour rendering index and high luminous efficacy. (May 2018) - Zhou, Z; Wang, H; Zhang, J; Su, J; Ge, P
Existing white light LED technology uses a blue light LED chip to stimulate a phosphor powder to form white light. The phosphor layer on the surface directly affects the colour rendering index, luminous efficacy and colour temperature of the LED. We propose a high power, white LED, chip-on-board package technology to achieve high colour rendering index and high luminous efficacy by optimising the spectral power distribution. The chip-on-board package light source can achieve a colour rendering index over 90 and a luminous efficacy over 90 lm/W while the power is 45W. It can be widely used in commercial lighting applications.